Analysis of the Role of Apron Movement Control (AMC) Officers in Handling Foreign Object Debris (FOD) to Improve Aviation Safety at Komodo Labuan Bajo Airport - Elizabeth Lusitania Yulita Jawa Towa; Faiz Albanna (CV. Rayyan Dwi Bharata, 2023)
Foreign Object Debris (FOD) are foreign objects that are animate and inanimate around the airside area which can cause damage to aircraft during landing and take off. The role of Apron Movement Control (AMC) in handling Foreign Object Debris (FOD) at Komodo Labuan Bajo Airport in order to avoid the risk of accidents for air transportation. This research uses qualitative. The data collected using observation (direct observation), interviews and documentation. After obtaining the required data, the researcher processed the data through several stages, namely data reduction, data presentation, and drawing conclusions. Based on the research results obtained by researchers, the role of Apron Movement Control (AMC) officers in handling Foreign Object Debris (FOD) to improve flight safety at Komodo Labuan Bajo Airport has been carried out in accordance with the SOP (Standard Operating Procedure) that applies at the airport. Obstacles that are often faced by Apron Movement Control (AMC) officers when handling Foreign Object Debris (FOD) to ensure flight safety at Komodo Labuan Bajo Airport, the most common of which is gravel or asphalt scraping, then nails, metal, luggage tags are found. , fruit peel, there are also animals such as dogs that get into the apron. This is Foreign Object Debris (FOD) found at Komodo Labuan Bajo Airport. Apron Movement Control (AMC) officers handle Foreign Object Debris (FOD), namely they check and clean around the apron area.